The role of sharia banking communication in strengthening decision making's factors - Fania Mutiara Savitri; Fika Safitri; Kartika Yunita; Endah Puspa Setyari; Osman Erdem Yapar (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2022)
Bank Syariah Indonesia (BSI) is the new brand from the merger of three Banks: BRI Syariah, BNI Syariah and Bank Mandiri Syariah. The leaders face the difficulties to manage every decision and human resource harmonization in branch level because of culture on each bank. This research was conducted to determine the effect of emotional intelligence professionalism and participatory leadership on participatory leadership with communication as a moderating variable. The research method in this study is a quantitative method. The population of this study was 100 employees of the BSI with the sampling technique using purposive sampling. The analysis used is in the form of SEM analysis using the PLS application. The results of this study indicate that the emotional intelligence of professionalism and participatory leadership has no effect on participatory leadership. Meanwhile, after being moderated by communication, the emotional intelligence, professionalism and participatory leadership have effects on decision making. Main conclusion is collaboration requires communication. This study has implications for the importance of a communication model based on Islamic values in managing Islamic institutions/organizations.***Bank Syariah Indonesia (BSI) merupakan brand baru dari penggabungan tiga Bank: BRI Syariah, BNI Syariah dan Bank Mandiri Syariah. Para pemimpin menghadapi kesulitan untuk mengelola setiap keputusan dan harmonisasi sumber daya manusia di tingkat cabang karena budaya di masing-masing bank. Penelitian ini dilakukan untuk mengetahui pengaruh profesionalisme kecerdasan emosional dan kepemimpinan partisipatif terhadap kepemimpinan partisipatif dengan komunikasi sebagai variabel moderasi. Metode penelitian dalam penelitian ini adalah metode kuantitatif. Populasi penelitian ini adalah 100 pegawai BSI dengan teknik pengambilan sampel menggunakan purposive sampling. Analisis yang digunakan berupa analisis SEM dengan menggunakan aplikasi PLS. Hasil penelitian ini menunjukkan bahwa kecerdasan emosional profesionalisme dan kepemimpinan partisipatif tidak berpengaruh terhadap kepemimpinan partisipatif. Sedangkan setelah dimoderatori oleh komunikasi, kecerdasan emosional, profesionalisme dan kepemimpinan partisipatif berpengaruh terhadap pengambilan keputusan. Kesimpulan utama penelitian ini adalah kolaborasi menyaratkan komunikasi. Studi ini berimplikasi terhadap pentingnya suatu model komunikasi berbasis nilai-nilai Islam dalam mengelola lembaga/organisasi keislaman.